Enraizamiento en álamo : Influencia de la epoca de extracción y del lavado de las estacas - Trione, Sinibaldo Oscar (1963)
Rooting in poplar. 1 lnfluence of the time of taken cuttings and their washing process to the rooting capacity. The object of this paper is to determine which is the best time to take cuttings, in Populus alba cv. "Bolleana", that would express its best rooting capa city. The cuttings were taken every 30 days during 1 months. At the same time it was included a variable consisting of washing the physiological base of the cuttings in tap water during 96 hours. Jn cuttings which were not washed it was determined the activity of water soluble inhibitors, as well as their moisture content. The best time to take cuttings for propagation is that of the dormancy period,, being July at it best with 100 % of rooting and 10 roots per cuttings. The washing operation increases not only the rooting capacity but the period of taking cuttings. There was no rorrelation among water soluble inhibitors activity on one hand and cuttings moisture content on the other, with the rooting capacity. The authors presume that the observed diffe. rences were due to the different ratios of natural auxins /cofactors present in the cuttings according to the collecting season, which in harmonious equilibrium favours the differenciation into root primordia. The washing process would facilitate this internal readjustement.